Character modeling - Dacol, Cesar, Jr., ....-; Hellard, Paul, ....-; Nakpil, Giovanni, ....-; Van Beek, Jan-Bart, ....-; Wade, Daniel, ....-; White, Gemma, ....- (Adelaide, South Australia. : Ballistic Publishing, 2009)
D'artiste Character Modeling is a definitive 3-D character tutorial book showcasing the astonishing work and technical skills of master artists Pascal Blanché, Francisco A. Cortina, and Steven Stahlberg. Each artist demonstrates their character modeling techniques through a series of tutorials taking different models from concept to creation.
Vol.3
Includes index.
Keywords: Computer drawing; Datoranimation; Computer animation